2015
DOI: 10.4274/tjo.39260
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pattern Electroretinography and Optical Coherence Tomography Parameters in Patients with Primary Open-Angle Glaucoma and Ocular Hypertension

Abstract: Objectives:To investigate the correlation of visual field (VF), pattern electroretinography (PERG) and Fourier domain optical coherence tomography (FD-OCT) results in patients with ocular hypertension (OHT) and early primary open-angle glaucoma (POAG).Materials and Methods:The study included 72 eyes of 37 patients with early POAG, 76 eyes of 38 patients with OHT, and 60 eyes of 30 controls. All subjects underwent full ophthalmologic examination, VF assessment with 24-2 Humphrey standard automated perimetry (Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
2
0
3
Order By: Relevance
“…They did not, however, include P50 or N95 latency in their study. Additionally, North et al 34 showed that, in comparison to the control group, the P50-N95 amplitude provided slightly better discrimination between 37 the N95 amplitude was lowered more than the P50 amplitude in the POAG and OHT groups compared to the control group. Also, they found that PERG amplitude analysis could detect ganglion cell dysfunction in OHT patients before OCT or visual field problems.…”
Section: Discussionmentioning
confidence: 99%
“…They did not, however, include P50 or N95 latency in their study. Additionally, North et al 34 showed that, in comparison to the control group, the P50-N95 amplitude provided slightly better discrimination between 37 the N95 amplitude was lowered more than the P50 amplitude in the POAG and OHT groups compared to the control group. Also, they found that PERG amplitude analysis could detect ganglion cell dysfunction in OHT patients before OCT or visual field problems.…”
Section: Discussionmentioning
confidence: 99%
“…Even Oli et al 22 in July 2015 and Fujimura et al 23 in Nov 2015 conducted similar studies on Cirrus HD OCT concluded that OCT could only be used as a supplementary tool to RNFL analysis. In Dec 2015, Demir et al 24 tried to elucidate a correlation between visual fields, pattern electroretinography (pERG) and FD-OCT parameters in patients with POAG and ocular hypertension (OHT). They concluded that the dysfunction due to GCC loss may be detected earlier using PERG analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[32] в глазах с офтальмогипертензией получено значительное уменьшение по сравнению с контролем амплитуды N95 (p < 0,0002) и отношения амплитуд N95/P50 (p < 0,002), но пиковые латентности волн P50 и N95 были в пределах нормы. В других исследованиях также показано статистически значимое снижение по сравнению с контрольной группой амплитуды P50 и N95 при преимущественном угнетении N95 [33]. В исследованиях М.В.…”
Section: результатыunclassified